PENGARUH MODEL PEMBELAJARAN INQUIRY TERHADAP HASIL BELAJAR IPAS MATERI ORGAN TUBUH MANUSIA KELAS V SD NEGERI 040448 KABANJAHE - Yustina Yusnidar Giawa; Johannes Keliat; Yosefo Gule (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Inquiry learning model on students’ learning outcomes in Natural and Social Sciences (IPAS) on the topic of human body organs among fifth-grade students at SD Negeri 040448 Kabanjahe. This research employed a quantitative approach using an experimental method. The research design was a quasi-experimental design with a nonequivalent control group design. The research sample consisted of two classes: class V-A as the experimental group with 35 students and class V-B as the control group with 29 students. The research instrument used was a multiple-choice test consisting of 25 items that had been tested for validity and reliability. Data were collected through pretest and posttest. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing with a t-test using SPSS version 22. The results showed that the average posttest score of the experimental class was 81.57, which was higher than the control class average score of 70.34. The hypothesis test result showed a significance value of 0.001 (< 0.05), indicating that H₁ was accepted and H₀ was rejected. Therefore, it can be concluded that the Inquiry learning model has a significant effect on students’ learning outcomes in IPAS on the topic of human body organs for fifth-grade students at SD Negeri 040448 Kabanjahe.